Minimally invasive percutaneous endoscopic discectomy and drainage for infectious spondylodiscitis - Tsai-Sheng Fu; Lih-Hui Chen; Wen-Jer Chen (Biomedical Journal, 2013)
The primary goals for treating infectious spondylodiscitis are to make an accurate diagnosis, isolate the causative organism, and prescribe effective antibiotic therapy based on the culture data. A positive culture of the responsible organism is not required for diagnosis, although it is extremely important for successful treatment and prevention of further morbidity. Surgical intervention is usually reserved for cases that are unresponsive to antibiotic therapy and for patients who have developed progressive spinal deformity or instability, epidural abscesses, or neurological impairment. However, the incidence of perioperative morbidity is particularly increased in elderly patients or in those with poor general condition. With improved endoscopic instruments and techniques, our clinical experiences demonstrate that spinal infections can be successfully treated by minimally invasive percutaneous endoscopic debridement. Direct endoscopic observation and collection of sufficient quantities of samples for microbiological examinations from the infected region are usually possible. This article summarizes the diagnostic and therapeutic values of percutaneous endoscopic discectomy and drainage (PEDD) used to treat patients with spondylodiscitis. Our clinical evidence-based survey suggests that PEDD can provide adequate retrieval of specimens and has high diagnostic efficacy, thereby enabling prompt and sensitive antibiotic therapy to the offending pathogens. We propose that PEDD is an effective alternative for treating infectious spondylodiscitis and should be considered prior to extensive anterior surgery in selected cases. This method is particularly suitable for patients with early-stage spinal infection or serious medical conditions.